THE ROLE OF TOXIC LEADERSHIP AND ANXIETY ON LECTURER MOTIVATION PERFORMANCE - Nainggolan, Christy Ruth Titiari; Puhi, Sitti Rojiyah Nur Insyirah; Sekarrini, Laras Ayu (Elsia: Jurnal Psikologi Manusia, 2025)
Lecturers, as educators and teaching staff, play a crucial role in improving the quality of education, reflecting their performance. However, toxic leadership and anxiety can impact lecturer performance. This study aims to determine the impact of toxic leadership and anxiety on lecturer performance using a quantitative ex post facto study of lecturers and teaching staff in higher education. The study found that toxic leadership and anxiety consistently impacted their performance, leading to a decline in performance if lecturers and teaching staff experience these issues continuously.